DILEMA IKLAN ROKOK DAN PERILAKU MEROKOK REMAJA - SISKAEVIA, SISKAEVIA (Jurnal Keolahragaan JUARA, 2022)
Adolescents in Palangkaraya had exposed by cigarette advertising for every day. The higher the intensity and if someone often sees the cigarette advertising with a large size, it will affect the perceptions of adolescents and finally have an impact to the smoke’s decision. The aim of the research is to describe adolescents’ perceptions of cigarette advertising and the implication and the implication for adolescents’ health behaviour. Method. This research use qualitative method, the subject of this research are 7 schools in the area of education in Palangkaraya City. The results showed that the adolescents perception of cigarette advertising is advertising that appeals to teenagers because it displays the theme and concept of advertising in accordance with the characteristics of young people, in addition to the advertising of cigarettes also sparked the curiosity of young people to try smoking and give an information about new tobacco product to adolescents, especially adolescent smoker. The enforcement of regulation on cigarettes and cigarette advertising, increased the education about smoking for students and teacher and build cooperation between every related sectors is the efforts to reduce the adolescents’ smoking behaviour.